Tourists’ perception using sentiment analysis at Cenang Beach - Abdul Latif, Samshul Amry; Khairul Azman, Khairul Ikhwan; Ramdzan Ali, Al Amirul Eimer; Matyakubov, Umidjon (AMER & cE-Bs by e-International Publishing House, 2025)
The increasing use of online platforms has made user-generated content vital for understanding tourist behavior. This study analyzes 460 English reviews from TripAdvisor about Cenang Beach, Langkawi, Malaysia, using thematic and sentiment analysis to identify factors influencing tourist satisfaction. Six key themes emerged: atmosphere, beach quality, activities, facilities, cleanliness, and health and safety. Positive reviews highlighted atmosphere and beach quality, while negative reviews focused on cleanliness and facilities, indicating areas for improvement. The findings offer insights for destination managers to enhance tourist experiences and maintain Langkawi's reputation as a top travel destination. Future research should include other languages and platforms.